Fatal course of veno-occlusive disease of the liver (endophlebitis hepatica obliterans) in a preterm infant - Sergi, Consolato M.; Beedgen, Bernd; Linderkamp, Otwin; Hofmann, Walter J. (Pathology, research and practice, 2011)
We describe the fatal course of a preterm infant of 34 weeks' gestation witb veno-occlusive disease of the liver and refractory ascites. Despite aggressive medical management, the baby died twenty-two hours post parIum because of cerebral haemorrhage before potentially life-saving organ transplantation could take place. At autopsy, paucity of lymphoid tissue in lymph nodes, thymus, spleen, and gastrointestinal tract were also seen. To our knowledge, this is the youngest infant with veno-occlusive disease of the liver reported in the literature.
Available online 1 November 2011
Gesehen am 29.12.2020